2017
DOI: 10.1128/jvi.01715-16
|View full text |Cite
|
Sign up to set email alerts
|

VP24-Karyopherin Alpha Binding Affinities Differ between Ebolavirus Species, Influencing Interferon Inhibition and VP24 Stability

Abstract: Zaire ebolavirus (EBOV), Bundibugyo ebolavirus (BDBV), and Reston ebolavirus (RESTV) belong to the same genus but exhibit different virulence properties. VP24 protein, a structural protein present in all family members, blocks interferon (IFN) signaling and likely contributes to virulence. Inhibition of IFN signaling by EBOV VP24 (eVP24) involves its interaction with the NPI-1 subfamily of karyopherin alpha (KPNA) nuclear transporters. Here, we evaluated eVP24, BDBV VP24 (bVP24), and RESTV VP24 (rVP24) interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…We have previously shown that RESTV is less capable than EBOV of counteracting IFN responses in Huh7 cells (41), suggesting a complex correlation between IFN antagonism and virus control in specific cell types. Along those lines, studies on the ebolavirus IFN antagonists VP35 and VP24 provide evidence that RESTV VP35 and VP24 might be less efficient in counteracting the IFN response (19,23,24,(69)(70)(71). It is likely that multiple factors contribute to the reduced pathogenicity of RESTV, and our data indicate that the lack of TLR4 activation might be one of them.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…We have previously shown that RESTV is less capable than EBOV of counteracting IFN responses in Huh7 cells (41), suggesting a complex correlation between IFN antagonism and virus control in specific cell types. Along those lines, studies on the ebolavirus IFN antagonists VP35 and VP24 provide evidence that RESTV VP35 and VP24 might be less efficient in counteracting the IFN response (19,23,24,(69)(70)(71). It is likely that multiple factors contribute to the reduced pathogenicity of RESTV, and our data indicate that the lack of TLR4 activation might be one of them.…”
Section: Discussionmentioning
confidence: 54%
“…EBOV is known to efficiently suppress the type I interferon (IFN) response and expresses at least two IFN antagonists, the viral protein 35 (VP35) and VP24 (reviewed in references 17 and 18). RESTV VP35 and VP24 have also been shown to antagonize the type I IFN response, albeit less efficiently (19)(20)(21)(22)(23)(24). The primary in vivo target cells of ebolaviruses are thought to be cells of the mononuclear phagocyte system, including monocytes, macrophages, and myeloid dendritic cells (9,25).…”
mentioning
confidence: 99%
“…Thus, it appears that NES activity is important for species of the genus Ebolavirus and Cuevavirus, but not Marburgvirus. Interestingly, MABV VP24 is unique among the VP24 proteins of filoviruses in that it is reported not to bind Ks (26,44,45). Thus, MABV VP24 would appear not to have the same requirement for interaction with nuclear trafficking machinery as the VP24 proteins of the other filoviruses.…”
Section: Vp24mentioning
confidence: 99%
“…VP24 binds competitively to this site, inhibiting nuclear import of STAT1, as well as other cellular cargoes that use the same site, but not cargoes that bind elsewhere (17,18,20,25). The interaction between VP24 and K has been the subject of intense research, revealing a well-defined VP24-K interface involving contact via three clusters of residues in VP24, with importance to IFN antagonism (19,20) and VP24 stability (26).…”
mentioning
confidence: 99%
“…VP24 from all ebolaviruses, but not MARV VP24, inhibit IFN signaling, although BDBV and RESTV VP24 are less efficient at inhibition. This may in part be due to decreased KPNA binding (Guito et al 2016;Schwarz 2016). LLOV VP24 inhibits the IFN pathway in a manner similar to EBOV VP24 by inhibiting IFN-induced STAT1 nuclear translocation and ISG induction presumably due to its ability to bind KPNA (Feagins and Basler 2015).…”
Section: Inhibition Of Nuclear Transport Of Stats-mentioning
confidence: 99%